High performance concrete with energetically modified cement (EMC) - Elfgren, Lennart; Jonasson, Jan-Erik; Ronin, Vladimir (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2004)
The demands of the modern building industry require development of new types of binder materials with improved properties for high and ultra high strength concretes and with significantly improved durability. They will provide new potential possibilities for the controlling of high performance concrete technology. In the Department of Civil Engineering at Luleå University of Technology a study of energetically modified cement (EMC) indicates that it is possible to obtain much more rapid hardening cement than the original cement used. As an example the strength of EMC-concrete increases about 100 per cent at the age of one day compared with a conventional high strength concrete.A new type of the cement gives possibilities to obtain required workability of the concrete mixtures with low water to binder ratios (w/B < 0.24) and achieve the strength levels up to 200 MPa with binder content not exceeding 550 kg/m3. The modification process used in this study means a special mechanochemical treatment in vibrating milling equipment of the blend containing Ordinary Portland Cement (OPC) and silica fume (SF), which increases the surface energy and the chemical reactivity of the newly obtained binder. This results in an accelerating effect, which maintains at least for nine months. According to ongoing investigations the energetically modified cement appears to give a considerable acceleration effect in the whole range of studied temperature. Concretes produced with EMC cement demonstrated very high durability at very severe testing conditions, including drying, saturation in sodium chloride solution and freezing-thawing. These results are very promising and it might be used in a lot of applications as winter concreting, precast element production, special structural elements, repair of buildings, rehabilitation, topping of concrete, floors, roads, etc. Godkänd; 2004; 20090203 (elfgren)